Pore Pressure Estimation Using Sonic Log and Eaton Method:Well YCG-P2A Case Study - Devano Ramadhan; Muhammad Rasyd Ridho; Muhammad Aqil Adib; Pasu Pradasari Purba; Gabe Bagus Arthantha; Cendikia Laisatara; Yolanda Tryana Sitorus (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2026)
Pore pressure prediction is an essential aspect of drilling planning to minimize the risks of kick, blowout, and lost circulation during drilling operations. This study focuses on estimating the pore pressure profile of Well YCG-P2A using sonic log data processed with the Eaton method. Sonic log responses from stable shale intervals were utilized to establish the Normal Compaction Trend (NCT), which served as the basis for pore pressure calculation within the depth range of 1,000–6,470 ft. Overburden stress was derived from density log integration, while hydrostatic pressure was calculated using a standard formation fluid gradient. The Eaton equation was then applied to generate a continuous pore pressure profile throughout the analyzed interval. The results show that pore pressure generally follows the hydrostatic trend, indicating predominantly normal pressure conditions across most of the well section. However, a localized decrease below hydrostatic pressure is observed at depths of approximately 3,500–3,700 ft, suggesting a possible underpressure anomaly. In contrast, pore pressure gradually increases above hydrostatic conditions within the 5,300–6,200 ft interval, indicating the presence of mild-to-moderate overpressure likely associated with undercompaction and restricted pore fluid expulsion. The Eaton method demonstrated good capability in identifying pressure variations and potential anomalous zones in Well YCG-P2A, although several intervals required careful interpretation due to log quality limitations and signal noise. Further calibration using direct formation pressure measurements, such as core analysis, Repeat Formation Tester (RFT), Modular Dynamics Tester (MDT), or Drill Stem Test (DST), is recommended to improve the reliability of the estimation results. Overall, this study provides a useful reference for mud weight determination, casing design, and drilling planning in Well YCG-P2A and adjacent wells within the same formation.